STANDARISASI KEKERASAN DALAM RUMAH TANGGA DALAM PERSPEKTIF HUKUM KELUARGA ISLAM - Kadir, Abdul (al-Rasῑkh: Jurnal Hukum Islam, 2023)
The aim of this study is to look at the standardization of domestic violence from the perspective of Islamic Family Law, in particular according to Mazhab Syafi’i, as well as the positive laws in force in Indonesia. KDRT is a serious problem that affects victims as well as families and society as a whole. As a Muslim-majority country, Indonesian law incorporates positive laws and Islamic values. This research uses qualitative methodology. Data in this research was collected through the study of literature from a variety of relevant sources, including books, journals, and legal documents. Mazhab Syafi’i’s view and positive law on the definition, legal action, and sanctions of the KDRT compared. The results of the research show that the KDRT is recognized by both Indonesian positive law and Mazhab Syafi’i as an act that violates the principles of justice and household welfare. However, there are differences in the way they deal with the KDRT issue and its enforcement. Through the integration of the perspective of Islamic law and positive law, the research is expected to make a significant contribution to the prevention and management of KDRT efforts in Indonesia, as well as improving protection and justice for KDRT victims. The benefits of the research include theoretical contributions to legal literature, improvement of public policy, empowerment of the public, and improved access to justice for the victims of the KDRT.